Astronomical spectroscopy for amateurs - Harrison, Ken M. (Patrick Moore's Practical Astronomy Series, 2011)
Astronomical Spectroscopy for Amateurs is a complete guide for amateur astronomers who are looking for a new challenge beyond astrophotography. The book provides a brief overview of the history and development of the spectroscope, then a short introduction to the theory of stellar spectra, including details on the necessary reference spectra required for instrument testing and spectral comparison. The various types of spectroscopes available to the amateur are then described. Later sections cover all aspects of setting up and using various types of commercially available and home-built spectroscopes, starting with basic transmission gratings and going through more complex models, all the way to the sophisticated Littrow design. The final part of the text is about practical spectroscope design and construction. This book uniquely brings together a collection of observing, analyzing, and processing hints and tips that will allow the amateur to build skills in preparing scientifically acceptable spectra data. It covers all aspects of designing, constructing, testing, calibrating, and using a spectroscope and enables the average amateur astronomer to successfully build and use a homemade spectroscope for a fraction of the current commercial cost. As Professor Chris Kitchin said, If optical spectroscopy had not been invented then fully 75 percent of all astronomical knowledge would be unknown today, and yet the subject itself receives scant attention in astronomical texts. This book answers that need. It is the practical spectroscopy book that amateur astronomers have been waiting for!